MicroRNA‐411‐3p inhibits bleomycin‐induced skin fibrosis by regulating transforming growth factor‐β/Smad ubiquitin regulatory factor‐2 signalling. Issue 24 (15th November 2021) - Zhang, Ziyan; Gao, Xuemin; He, Yang; Kang, Yumeng; Jin, Fuyu; Li, Yaqian; Li, Tian; Wei, Zhongqiu; Li, Shifeng; Cai, Wenchen; Mao, Na; Wang, Shan; et al.
Abstract: Skin fibrosis, which is characterized by fibroblast proliferation and increased extracellular matrix, has no effective treatment. An increasing number of studies have shown that microRNAs (miRNAs/miRs) participate in the mechanism of skin fibrosis, such as in limited cutaneous systemic sclerosis and pathological scarring. The objective of the present study was to determine the role of miR‐411‐3p in bleomycin (BLM)‐induced skin fibrosis and skin fibroblast transformation. Using Western blot analysis and real‐time quantitative polymerase chain reaction assess the expression levels of miR‐411‐3p, collagen (COLI) and transforming growth factor (TGF)‐β/Smad ubiquitin regulatory factor (Smurf)‐2/Smad signalling factors both in vitro and in vivo with or without BLM. To explore the regulatory relationship between miR‐411‐3p and Smurf2, we used the luciferase reporter assay. Furthermore, miR‐411‐3p overexpression was identified in vitro and in vivo via transfection with Lipofectamine 2000 reagent and injection. Finally, we tested the dermal layer of the skin using haematoxylin and eosin and Van Gieson's staining. We found that miR‐411‐3p expression was decreased in bleomycin (BLM)‐induced skin fibrosis and fibroblasts. However, BLM accelerated transforming growth factor (TGF)‐β signalling and collagen production. Overexpression of miR‐411‐3p inhibited the expression of collagen, F‐actin and the TGF‐β/Smad signalling pathway factors in BLM‐induced skin fibrosis and fibroblasts. In addition, miR‐411‐3p inhibited the target Smad ubiquitin regulatory factor (Smurf)‐2. Furthermore, Smurf2 was silenced, which attenuated the expression of collagen via suppression of the TGF‐β/Smad signalling pathway. We demonstrated that miR‐411‐3p exerts antifibrotic effects by inhibiting the TGF‐β/Smad signalling pathway via targeting of Smurf2 in skin fibrosis.